ANALISIS PROXIMATE UNTUK MENENTUKAN KUALITAS BATUBARA DI PT.GEOSERVICES KECAMATAN TANJUNG REDEB KABUPATEN BERAU PROVINSI KALIMANTAN TIMUR - Elta rani kalimbuang; Hendra Sani; Kasmira (Fakultas Teknik UPRI, 2025)
The purpose of this study to determine the quality of coal in terms of proxymate analysis of the results of the analysis of samples by using the ISO standard and ASTM. The Oversight data collection was done by testing samples of 6 samples in the PT.Geoservices laboratory. Based on the results of the testing showed that the testing moisture at sample using standard ASTM showed 14:09%, 13:51%, 10:22%, 13.83%, 14:11%, 14:11%, 14:01% and for ISO 13:06%, 13:00%, 12.96 %, 12.98% 12.90%, 13.08%, 12.94%. Based on data analysis, can be Conculated that the data in the analysis is Coal Sub-Bituminous ranged between 10% - 25%. Percentage of ash content of the test results in laboratory obtained percentage for the standard AST M is 7:52% 4:46%, 33.44%, 14:56% 4:34% 6:21% and to ISO 5:58% 5:48% 5:56%, 5.62% 5:56% , 5.64%. the percentage of volatile matter of the analysis results in laboratory obtained percentage for AST M standard is 41.11%, 44.45%, 30.81%, 39 .71%, 39.71%, 43.84%, 43.79% d late to the ISO standards are 37.10%, 37.32%, 37.00%, 37.16%, 36.92%, 37.19% fixed carbon grade not analyzed in laboratory but obtained from the calculation of indirect in getting the percentage for AST M 37.28%, 37.58% 25.53%, 31.90%, 37.71%, 35.99% and for ISO namely 44.26%, 44.20%, 44.46%, 44.32%, 44.44%, 44.23%. On Sample Coal studied in PT.Geoservices entered in the class of Coal Sub-Bituminous based classification of coal according to ASTM Standards, and Deserves to be marketed depending demand client.